Los tiempos de la modernidad. A propósito de Marshall Berman / Times of Modernity. Regarding Marshall Berman - Díaz Freire, José Javier (Historiografías, 2017)
Modernity, modernization and modernism have being scrutinized thoroughly in humanities since the 1990s. They bear the accusation of harbouring a normative content, which would render it not useful for social analysis. This essay states that in order to make those terms adequate for historiography, the concept of time that is at its core has to be openly discussed and even modified. To this purpose, the article regains the debates that followed the publication of All that is Solid Melts into the Air (1983) by Marshall Berman, and concludes that to free the concept of modernity from its constraints, a heterogeneous concept of time is needed, instead of the homogeneous one which has traditionally prevailed.Key WordsModernity, modernism, modernization, homogeneous time, hetero-temporality.ResumenLa modernidad y también la modernización y el modernismo han sido sometidos a un intenso escrutinio por parte de las humanidades desde los años noventa. Se les acusa de alojar un contenido normativo, lo que ha puesto en cuestión su utilidad para el análisis social. Este artículo sostiene que, para hacer de ellos términos adecuados para el análisis histórico, se debe discutir abiertamente e incluso modificar el concepto de tiempo que se contiene en dichas categorías. Para ello este artículo recupera el debate que suscitó la publicación del libro de Marshall Berman Todo lo sólido se desvanece en el aire (1982), y concluye que para liberar el concepto de modernidad de sus restricciones, la historiografía necesita de una idea de tiempo heterogéneo que sustituya al homogéneo que la ha caracterizado tradicionalmente.Palabras claveModernidad, modernismo, modernización, tiempo homogéneo, tiempo heterogéneo.